Implementation of Digital Forensics Photorec in Recovering Lost Files on External Storage - Dasmen, Rahmat Novrianda; Triwulanda, Asti; Rasmila, Rasmila; Kurniawan, Dedi; Julia, Julia (LPPM Universitas Islam 45 Bekasi, 2024)
Portable data storage devices, such as flash drives, are one of the most widely used data storage media today. It has a fairly large storage capacity and is easy to carry around. However, flash drives are also prone to damage, such as lost or deleted files. Damage to files on a pen drive can be caused by various factors, such as user error, viruses, or physical damage. File damage caused by user error, such as accidental deletion of files, can be easily repaired using file recovery software. One of the popular file recovery software is Photorec, which is an open-source software that can be used to recover various types of files, including photos, videos, documents, and other files. Photorec uses the file carving method to recover lost or deleted files. The file carving method is a file recovery method that works by looking for intact blocks of data within the storage media. These intact data blocks are then identified as specific files. This research aims to determine the effectiveness of Photorec in recovering lost files on a flash disk. This research uses an experimental method by simulating file corruption on a flash disk in Bina Darma University. File damage is done by accidentally deleting files. The results show that Photorec can recover lost files on flash drives with a high success rate. Photorec can recover lost files intact, including photos, videos, documents, and other files.